Design and development of an automatic car door opening and locking system - Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Irwan, I.; Azoa, A.; Adly, A. (2008)
The aim of this paper is to present an Automatic Car Door Opening-Closing (ADOC) system focus on giving a faster, safer and more reliable locking mechanism for the user. The design process includes integration of logic gate operations into the circuit diagram of the system and a perfect mechanism that used for opening-locking operation of the door. The system used a DC motor to operate the mechanism for a short period of time. Electromagnetic solenoid switches are used to control the circuit of the ADOC. The systems react-based-on sensor mechanism to increase the system safety aspect and determines the operation of the system. The ADOC system gives the optimum output with an operating time 5.02 s at normal load.